2018
DOI: 10.1093/ajcn/nqx048
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of remotely delivered interventions using self-monitoring or tailored feedback to change dietary behavior

Abstract: BackgroundSelf-monitoring (SM) of diet and tailored feedback (TF) have been suggested as tools for changing dietary behavior. New technologies allow users to monitor behavior remotely, potentially improving reach, adherence, and outcomes.ObjectiveWe conducted a systematic literature review and meta-analysis to address the following question: are remotely delivered standalone (i.e., no human contact) interventions that use SM or TF effective in changing eating behaviors?DesignFive databases were searched in Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 64 publications
0
62
1
Order By: Relevance
“…We used fixed‐effects models, if no heterogeneity existed among the 14 studies, and random‐effects models were used, when heterogeneity existed. To assess the robustness of the results, we performed a sensitivity analysis by omitting each study one by one . The false discovery rate (FDR) with a critical cut‐off value of 0.05 using the linear step‐up method of Benjamini and Hochberg was mainly used to correct for multiple comparisons to reduce the probability of false‐positive findings .…”
Section: Populations and Methodscontrasting
confidence: 59%
See 1 more Smart Citation
“…We used fixed‐effects models, if no heterogeneity existed among the 14 studies, and random‐effects models were used, when heterogeneity existed. To assess the robustness of the results, we performed a sensitivity analysis by omitting each study one by one . The false discovery rate (FDR) with a critical cut‐off value of 0.05 using the linear step‐up method of Benjamini and Hochberg was mainly used to correct for multiple comparisons to reduce the probability of false‐positive findings .…”
Section: Populations and Methodscontrasting
confidence: 59%
“…To assess the robustness of the results, we performed a sensitivity analysis by omitting each study one by one. 29 The false discovery rate (FDR) with a critical cut-off value of 0.05 using the linear step-up method of Benjamini and Hochberg was mainly used to correct for multiple comparisons to reduce the probability of false-positive findings. 30 To observe the combined effect of significant SNPs, we used the number of unfavorable genotypes (NUGs) of the significant SNPs as a genetic score to assess classification performance of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Participants from both samples reported lack of monitoring their food intake which further highlights "capability" as a barrier to uptake of the MIND diet. Previous research found that behaviour regulation was associated with changes in dietary outcomes [55] and more specifically, self-monitoring was associated with a positive change in diet [56,57]. Self-monitoring is shown to not only increase awareness of eating patterns [58,59], but also allows professionals to identify food aversions/intolerances and poor food choices [59].…”
Section: Discussionmentioning
confidence: 99%
“…Two interventions used a French online service (Minitel) which is no longer available. Another outdated technology, a personal digital assistant (PDA), was used in 2008 (64) . The study conducted by Campbell et al did not have human contact during the nutritional feedback but used software installed in the offices where the study was conducted (65) .…”
Section: Technologies Used In Remotely Delivered Nutrition Interventionsmentioning
confidence: 99%
“…Web application [1] Source: Adapted from [64] . Considering only interventions using computer technology and classifying these systems.…”
Section: Conflict Of Interestmentioning
confidence: 99%